Factors influencing students to buy cosmetic and beauty care products online / Asphelaila Sang - Sang, Asphelaila (Faculty of Business and Management, 2018)
The revolution of the internet has changed the way people do their business. This research study aims to identify the factors influencing students in Kuching area to purchase cosmetics and beauty care products online. This study intends to examine the relationship of privacy, convenience, online banking, website credibility, price and social media with online shopping decision. Students between the age of 18 to 30 years old were selected randomly in Kuching as respondents of analysis. 200 questionnaire were answered and valid for coding and analysis. Collected data were analyzed using SPSS version. The findings of this study show that all six elements have significant relationship with online shopping decision. The results show that social media is the main contributing factor influencing students to purchase online.